PENGEMBANGAN BAHAN AJAR PERKALIAN PECAHAN BIASA BERBENTUK HANDOUT PADA SISWA KELAS V SEKOLAH DASAR - Savira Maharani (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
This study aims to develop teaching materials for multiplying ordinary fractions in the form of handouts for fifth grade elementary school students. This handout teaching material was validated by material and design experts, practitioners and effectiveness test. The study was conducted at MIN 12 Medan with 10 fifth grade students as study subjects. This study used the development model by Thiagarajan and Sammel (1974), which has four phases: define, design, development, and dissemination. The instruments used in this study were material validation questionnaires, designs, practitioners, student responses, and pretest-posttest questions to determine the effectiveness of handout teaching materials. The results of the study explained that the handout teaching materials had passed the material expert assessment, design, practitioner, and field trial phases. The overall assessment average gets a final score of 88% with a very feasible category. In line with the assessment results, the teaching materials for multiplying ordinary fractions in the form of handouts for grade V elementary school students that have been developed are suitable for use.